New high yielding sesame (Sesamum indicum L.) variety Phule Purna for Maharashtra: NEW HIGH YIELDING SESAME VARIETY PHULE PURNA FOR MAHARASHTRA - M R BEDIS; Y G PATIL; T R PATIL; R S BHADANE; S D RAJPUT (Journal of Oilseeds Research, 2024)
Sesame is one of the important oilseeds crop requiring low inputs. The productivity of summer sesame is very low in Maharashtra state. The present improved varieties of sesame have lower yield potential and disease susceptibility. That is why need to develop high yielding varieties combined with early to mid-synchronous maturity, better quality and resistance to major pests and diseases. The new culture JLT-408-2 for summer season is advance generation selection from the cross JLT-26 x KMR 90 at Oilseeds Research Station, Jalgaon. It was tested over several locations and environments for its stability performance. The results indicated a significant improvement in yield level under field conditions. On an average performance of 55 station, multilocation, coordinated and adaptive trials conducted during 2014 to 2020.The new culture Phule Purna recorded 752 kg/ha yield as against the check JLT-408 (581 kg/ha), TKG-22 (622 kg/ha), AKT-101 (635 kg/ha), PT-1 (636 kg/ha) and GT-10 (673 kg/ha) which was higher by 22%, 14%, 12%,11.94 and 3.71 per cent increase over, respectively. This new culture is white bold seeded and also found superior in quality viz., oil content (Av. 49.02%) as compare to PT-1 (47.58%), JLT-408 (45.16%), (GT-10 (44.82%) and AKT-101 (44.58%). FFA%: 0.81% as compare to PT-1 (2.80%), JLT-408 (1.60%) and AKT-101 (1.10%). Iodine Value: 106.8 as compare to PT-1 (108%), JLT-408 (107%) and AKT-101 (106.8%).